Metal Residues in Retail Chicken Meat at Shivamogga, Karnataka : 10.5958/2581-6616.2020.00017.1 - Karabasanavar, Nagappa S.; Sivaraman, G.K.; P.S., Girish (Journal of Meat Science, 2020)
Environmental pollution and contravenes in safe and hygienic production have led to contamination of animal origin foods with toxic residues. Occurrence of metal residue contamination in chicken meat poses considerable risk to the human health leading to a spectrum of health related issues. Owing to their public health concerns, market chicken meat samples were analyzed for metal or heavy metal residues. Breast muscle samples collected from retail outlets of Shivamogga city (Karnataka) were digested using nitric acid: per chloric acid and quantitatively analyzed using graphite furnace atomic absorption spectrophotometer (GFAAS). Concentrations of metal residues were expressed as mean ± S.D. range (mg. kg-1) viz. Chromium (0.0272±0.0092; 0.0178-0.0515), Copper (0.1004±0.0638; 0.022-0.2199), Iron (2.3247±1.9029; 0.2815-6.9505), Lead (0.0297±0.0107; 0.0083-0.0495), Magnesium (0.1573±0.0337; 0.0949-0.2317), Manganese (0.0740±0.0508; 0.0135-0.1416), Nickel (0.0257±0.0446; 0-0.0822), Tin (0.8296±0.2007; 0.4870-1.3883), Zinc (0.9001±0.3832; 0.2805-1.4988) and Cadmium (not detected). Residue levels found in chicken breast meat samples were within prescribed maximum residue limits (MRLs) of Codex/FAO/WHO and FSSAI for all the ten metal/ heavy metal concentrations. Present study establishes occurrence of metal residues in chicken meat and underscores need for framing national guidelines/ standards for these toxic metals in various kinds of meat and meat products.
Keywords: Heavy metals; Residue; Food; GFAAS; Analysis; Acid digestion; Food safety